2011
DOI: 10.1007/s10554-011-9997-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in-stent neointimal tissue components using integrated backscatter intravascular ultrasound: comparison of drug-eluting stents and bare-metal stents

Abstract: Although in-stent restenosis (ISR) occurs after drug-eluting stents (DES) implantation, neointimal tissue characteristics have not been fully investigated. We assessed neointimal tissue components using integrated backscatter intravascular ultrasound (IB-IVUS) after DES and bare-metal stents (BMS) implantation. Fifty-seven consecutive patients with 61 lesions underwent repeated percutaneous coronary intervention (PCI) for the treatment of ISR (DES: 24 lesions, BMS: 37 lesions). PCI was performed using plain ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Muraoka et al demonstrated by integrated backscatter‐IVUS that intra‐DES neointima was associated with low integrated backscatter value (allegedly‐corresponding to lipid), which caused distal slow flow phenomenon after balloon angioplasty . Although absence of definition of necrotic tissue in integrated backscatter‐IVUS make it impossible to compare our observation with their results, our iMap and their integrated backscatter‐IVUS results are in agreement with that intra‐DES neointima was composed of less‐fibrotic and less‐stabilized tissue with a broader distribution of various tissue components as compared with intra‐BMS neointima.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Muraoka et al demonstrated by integrated backscatter‐IVUS that intra‐DES neointima was associated with low integrated backscatter value (allegedly‐corresponding to lipid), which caused distal slow flow phenomenon after balloon angioplasty . Although absence of definition of necrotic tissue in integrated backscatter‐IVUS make it impossible to compare our observation with their results, our iMap and their integrated backscatter‐IVUS results are in agreement with that intra‐DES neointima was composed of less‐fibrotic and less‐stabilized tissue with a broader distribution of various tissue components as compared with intra‐BMS neointima.…”
Section: Discussionsupporting
confidence: 86%
“…Taken together, in‐stent restenotic lesions may not be as stable as previously thought; and in vivo assessment of neointimal tissue component becomes more important than before because it was not clear why some in‐stent neoatherosclerosis culminated in acute coronary syndrome and some did not. Although IVUS and optical coherence tomography are potential modalities to assess the neointimal tissue in this moment , IVUS‐based tissue characterization modalities have more quantitative parameters as compared with qualitative neointimal assessment by optical coherence tomography.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, there was no significant difference between percentage lipid and fibrous neointima in DES restenosis as compared to BMS restenosis. These findings are consistent with the results of IB-IVUS analysis by Muraoka et al [22]. The discrepancy between the two modalities could be related to differences in definitions for tissue characterization.…”
Section: Comparison With Previous Study Utilizing Imapsupporting
confidence: 91%
“…Muraoka et al [22] have reported a subgroup of DES restenosis with low backscatter value (allegedly-corresponding to lipid) in which distal SF was observed after balloon angioplasty (POBA). In our study, SF occurred more frequently at MSA sites with a nonhomogeneous pattern where the percentage lipid neointima was found to be greater as compared to sites with a homogeneous pattern.…”
Section: Comparison With Previous Studies Utilizing Ib-ivusmentioning
confidence: 99%
“…An IB-IVUS study has also found neointima within BMS-associated lesions to contain mainly middle-IB tissue, suggesting fibrous tissue [20,21]. Luminal renarrowing of the stented segment has been reported to be a progressive process [22], and histopathological and imaging studies, such as virtual histology IVUS and optical coherence tomography, have demonstrated changes in neointimal tissue characteristics in the late phase after BMS implantation.…”
Section: Discussionmentioning
confidence: 99%